Earthquake time history for Dhaka, Bangladesh as competent seismic record - Saiful Islam, A.B.M.; Jameel, M.; Rahman, M.A.; Jumaat, Mohd Zamin (International Journal of Physical Sciences, 2011)
The time varying forces in the ground generates earthquake loads and the pattern of load specified as a time history of ground excitation is the most accurate means of representing earthquake actions. The difficulty with carrying out analysis procedures to compute the responses of a structure for this type of load is that the form of the acceleration time history is to be clearly known. As there is lack of earthquake data for Dhaka, Bangladesh, which is in risk of attack by severe earthquakes, the engendering earthquake time history data of this region for precise dynamic analysis is of utmost importance. So, the objective of this research is to develop the reliable Dhaka earthquake time history, functioning as a competent seismic record. Seismic data have been measured in-situ with proper seismographic instruments at the recently occurred local earthquake near the Dhaka vicinity. Choosing the nearby seismic record, probable acceleration time history of Dhaka has been properly scaled as per the seismicity and ground acceleration characteristics of its own, following the widely accepted Bangladesh National Building Code (BNBC). Generated EQ time history is then evaluated with the prominent seismic records available in literature. This seismic data essentially yield the responses at every little incremental state of numerous time extents. The research acquaints us with suitable Dhaka earthquake time history data which can be reliably exploited as advance future seismic record.